Competitiveness indices and developing countries : an economic evaluation of the global competitiveness - Lall, Sanjaya (2001)
Analyzes, from a development economics perspective, whether competitiveness is a legimate concern, and whether the leading indices reserve the attention they get. Assesses the best-known index - the Global Competitivenes Report of the World and finds deficiencies at several levels.